Knowledge Level of Midwives before and after an Online Training Participation - Windi Nurdiawan; Setyorini Irianti; Dyah Ayu Puspita; Alfonsus Zeus; Billy Nusa Anggara; Vebri Anita Sinaga; Wulan Ardhana Iswari; Will Hans; Eduward Yacub Prasangka; Fadhilah Zulfa (Universitas Islam Bandung, 2022)
Fetal growth restriction is a prevalent pregnancy issue linked to numerous unfavorable postnatal outcomes. Suboptimal uterine-placental perfusion and inadequate fetal feeding are the vital pathophysiologic causes. Midwives play a crucial role in informing pregnant women about vitamin D inadequacy. This paper aims to determine the difference between midwives' prior and post-webinar knowledge levels. It was a cross-sectional study of individuals who participated in a webinar on November 21, 2021. Subjects were selected using a total population sampling approach from all midwives who participated in the webinar and completed pre-and post-tests. The difference between knowledge levels was evaluated using the difference between the pre-test and post-test scores in the general category. There was an increase in the number of participants who successfully answered the five-question component, a decrease in the number of participants who correctly answered the two-question section, and no change in the number of subjects who correctly answered question number one. The average score on the post-test was higher (67.28) than the pre-test (63.10), while the median score was the same at both time points. After attending a webinar, there was an increase in the proportion of subjects with a high level of knowledge (11.4% to 24%) and a drop in the proportion of subjects with a poor level of knowledge (32.3% to 27.1%). In conclusion, there was an improvement in the knowledge level of midwives before and after the webinar participation.